Late eating, blood pressure control, and cardiometabolic risk factors among adults with hypertension: results from the Korea National Health and Nutrition Examination Survey 2010–2018 - Jee-Seon Shim; Hyeon Chang Kim (Epidemiology and Health, 2021)
OBJECTIVES Despite growing concerns regarding the timing of eating, little is known about the association between late eating and health. This study aimed to investigate whether late eating is associated with blood pressure (BP) control and cardiometabolic risk factors among Korean adults with hypertension. METHODS Data from the Korea National Health and Nutrition Examination Survey 2010–2018 were used. Adults with hypertension aged 30–79 years (n=13,361) were included in this study. Dietary intake and information on meal timing were assessed using 1-day 24-hour recall. Late eating was defined as after the median midpoint between the times of the first and the last eating episode during the recall day. Logistic and linear regression models were used to estimate the associations of late eating with BP control and cardiometabolic risk factors. RESULTS Among late eaters, there were more men than women. Compared to early eaters, late eaters were younger, had a higher body mass index (BMI) and unhealthier habits, and their overall dietary quality score was lower. A negative association between late eating and BP control was found in a univariate model (odds ratio [OR], 0.82; 95% confidence interval [CI], 0.94 to 1.12), but this association disappeared after adjustment for confounders (OR, 1.03; 95% CI, 0.94 to 1.12). Late eating was independently associated with higher BMI (p=0.03) and blood triglyceride concentration (p<0.01). CONCLUSIONS Our results do not support a link between late eating and BP control among adults with hypertension, but suggest that late eating is associated with cardiometabolic risk factors.